Consumer Values and Intention to Visit Food Truck “Angkringan” amidst Covid-19 Pandemic - Istiyawati Rahayu; Rahaju Muljo Wulandari; Rayhan Gunaningrat (ITB AAS INDONESIA, 2022)
The purpose of this study is to identify the factors that influence consumers' intention to visit the food truck “angkringan” from both utilitarian and hedonic perspectives. Structural equation modeling (SEM) was conducted with a sample of 42 responses. Both hedonic and utilitarian values do not directly impact consumers’ intention, but the values do trigger consumers’ intention indirectly by boosting a positive attitude toward food truck “angkringan”. Although utilitarian and hedonic values, such as convenience and reasonable prices, do not directly increase the intention to visit a food truck, these values evoke a favorable attitude towards the food truck which will ultimately trigger the intention. Thus, to attract consumers, utilitarian values e.g. efficiency or functionality and hedonic values, such as fun, exciting, unique, pleasant atmosphere, should not be ignored.